La competitività responsabile nelle PMI: Strategia vincente nei territori “nemici” - DeChiara, Alessandra (Piccola Impresa / Small Business, 2012)
The roots of this research lie in the awareness that there is a relationship of mutual interdependence between small and medium enterprises (SMEs) and the local system. These firms are strongly rooted in the territory from which they draw resources often not available inside the firms. The competitiveness of the territory positively influences the competitiveness of those enterprises able to establish relationships with the local actors. But what happens when the territory that was a fertile basis becomes an enemy? This research poses the hypothesis that corporate social responsibility (CSR) is introduced as an enterprise-level strategy to overcome the negative effects produced by the territory and to restore the level of competitiveness of the firm. In fact if the CSR efforts are organised in a synergistic way, they can create a virtuous path in which the enterprise efforts stimulate improvements in the local network, which then regenerates resources and competencies usable by the enterprises located within it.